1996
DOI: 10.1016/0375-9474(96)00218-7
|View full text |Cite
|
Sign up to set email alerts
|

Model calculations of doubly closed shell nuclei in CBF theory III. jj coupling and isospin dependence

Abstract: two-body Euler equations provide correlation functions variationally more effective than those obtained with the same technique in infinite nuclear matter.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
158
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(163 citation statements)
references
References 19 publications
4
158
1
Order By: Relevance
“…Bearing in mind that our results are fully variational it is clear that our TICI2(SD) calculation is better than any of the other results shown for 12 C with the B1 potential. We note also that the results based on a spherical assumption give appreciably less binding for 12 C. This is particularly so for the FHNC results [5] based on a jj coupling scheme. We show results for both the lowest-order FHNC/0 approximation of the Fantoni-Rosati scheme, in which all elementary diagrams are neglected, and for their FHNC-1 approximation in which the first-order elementary exchange diagram has been included.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Bearing in mind that our results are fully variational it is clear that our TICI2(SD) calculation is better than any of the other results shown for 12 C with the B1 potential. We note also that the results based on a spherical assumption give appreciably less binding for 12 C. This is particularly so for the FHNC results [5] based on a jj coupling scheme. We show results for both the lowest-order FHNC/0 approximation of the Fantoni-Rosati scheme, in which all elementary diagrams are neglected, and for their FHNC-1 approximation in which the first-order elementary exchange diagram has been included.…”
Section: Resultsmentioning
confidence: 66%
“…[5] and references cited therein for details). One drawback of this procedure is that certain cancellations between elementary exchange diagrams are thereby ignored.…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of Ref. [16] has shown that the main contribution to the one-body density matrix is given by ρ t 0 , which is the only term surviving in spin saturated systems having degenerate spin-orbit partners. The similarity of this term to the one appearing in the ls coupling scheme, allows us to use some simplifications in the calculations of the correlated distributions (9,10) following the procedure adopted in [25].…”
Section: The Formalismmentioning
confidence: 99%
“…This part of the calculation follows step by step that presented in [16]. The two-body densities are written in terms of the scalar correlation f 1 (r), of the nodal, or chain, diagrams N xy (r 1 , r 2 ), of the non nodal (composite) diagrams X xy (r 1 , r 2 ) and of the elementary, or bridge, diagrams E xy (r 1 , r 2 ).…”
Section: The Formalismmentioning
confidence: 99%